Altered Short-Term Synaptic Plasticity in Mice Lacking the Metabotropic Glutamate Receptor mGlu7. (2002) - Bushell, Trevor J.; Sansig, Gilles; Collett, Valerie J.; van der Putten, Herman; Collingridge, Graham L.
Abstract : Eight subtypes of metabotropic glutamate (mGlu) receptors have been identified of which two, mGlu5 and mGlu7, are highly expressed at synapses made between CA3 and CA1 pyramidal neurons in the hippocampus. This input, the Schaffer collateral-commissural pathway, displays robust long-term potentiation (LTP), a process believed to utilise molecular mechanisms that are key processes involved in the synaptic basis of learning and memory. To investigate the possible function in LTP of mGlu7 receptors, a subtype for which no specific antagonists exist, we generated a mouse lacking this receptor, by homologous recombination. We found that LTP could be induced in mGlu7-/- mice and that once the potentiation had reached a stable level there was no difference in the magnitude of LTP between mGlu7-/- mice and their littermate controls. However, the initial decremental phase of LTP, known as short-term potentiation (STP), was greatly attenuated in the mGlu7-/- mouse. In addition, there was less frequency facilitation during, and less post-tetanic potentiation following, a high frequency train in the mGlu7-/- mouse. These results show that the absence of mGlu7 receptors results in alterations in short-term synaptic plasticity in the hippocampus.